Democracy's guardians : a history of the German Federal Constitutional Court, 1951-2001 - Collings, Justin (Oxford : Oxford University Press, 2015)
In an examination of the German Federal Constitutional Court from its founding in 1951 up to the twenty-first century, this book presents an historical account of how the Court helped transform Germany from a pre-democratic political culture into one of the leaders of the liberal democratic world.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 22, 2015).
Keywords: Germany. -- Bundesverfassungsgericht -- History; Constitutional courts -- Germany